Robust large-area elastic transverse wave transport in active acoustic metamaterials - Chen, Zhenyu (2022)
We investigate robust large-area elastic transverse wave propagation in an actively tunable membrane-type acoustic metamaterial. The waveguide with multiple degrees of freedom to control the width of the interface mode is realized by designing a heterostructure including three domains. One central domain is constructed by periodic unit cells in an ordinary state, where a Dirac cone can be observed in the band structure. The other two domains consist of periodic unit cells possessing opposite valley Chern numbers, respectively. By employing a finite element model, the topologically protected interface states with tunable degrees of freedom are exhibited. The energy of interface states distributes equally in the large-central region. Although a larger degree of freedom leads to lower amplitudes of interface states, larger total energy is demonstrated by defining a quality factor. Moreover, we design several waveguides with straight lines and sharp corners with different angles and denote three different notations to show clearly that the large-area transverse wave can propagate robustly through sharp corners. Finally, it is found that the large-area transverse wave transport shows immunity to disorders and defects in the propagation path.